Heraldry of the Plains - Bonnie Lynn-Sherow (Symphony in the Flint Hills, 2013)
There are some striking connections between Army insignia or heraldry and the way in which Cheyenne, Lakota, and other Plains warriors decorated themselves, their horses, and their weapons before going into battle.
Keywords: Cheyenne Dog Soldier; Indian warriors; Kit Fox; Cheyenne; Lakota; Plains; horses; decorated; paint; ledger art; heroic; protection; regalia; Seventh Cavalry; flag; Fourth Reconnaissance Battalion; lance; insignia